2001
DOI: 10.1182/blood.v97.4.1144
|View full text |Cite
|
Sign up to set email alerts
|

Specialized roles of the chemokine receptors CCR1 and CCR5 in the recruitment of monocytes and TH1-like/CD45RO+T cells

Abstract: Chemokines and their receptors control the emigration of leukocytes during inflammation. The role of the RANTES (regulated on activation normal T-cell expressed and secreted) receptors CCR1 and CCR5 in the selective recruitment of monocytes, T(H)1-like T-cell clones, and peripheral T cells enriched for CD45RO(+) "memory" cells were tested in a system in which arrest under flow conditions is triggered by RANTES immobilized to activated endothelium. With the use of selective nonpeptide receptor antagonists or bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
188
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 237 publications
(200 citation statements)
references
References 24 publications
11
188
0
Order By: Relevance
“…In contrast, our data clearly demonstrate the nonredundant role of CCR1 (ligands CCL3 and CCL4) for renal leukocyte recruitment after UUO in mice. The finding that CCR1 is important for renal leukocyte recruitment in vivo is consistent with in vitro data showing that CCR1 but not CCR5 is essential for the initial leukocyte attachment to endothelium (14). Initial attachment mediated by CCR1 is therefore critical for renal leukocyte recruitment.…”
Section: Lack Of Ccr5 Expression Does Not Affect Leukocyte Infiltratisupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, our data clearly demonstrate the nonredundant role of CCR1 (ligands CCL3 and CCL4) for renal leukocyte recruitment after UUO in mice. The finding that CCR1 is important for renal leukocyte recruitment in vivo is consistent with in vitro data showing that CCR1 but not CCR5 is essential for the initial leukocyte attachment to endothelium (14). Initial attachment mediated by CCR1 is therefore critical for renal leukocyte recruitment.…”
Section: Lack Of Ccr5 Expression Does Not Affect Leukocyte Infiltratisupporting
confidence: 79%
“…In vitro studies have suggested different roles of CCR1 and CCR5 for leukocyte recruitment. CCR1 but not CCR5 was found to be required for the initial adhesion of human monocytes and T cells to activated endothelium, whereas CCR5 seemed to be involved in the subsequent transendothelial cell migration (14).…”
mentioning
confidence: 99%
“…We have previously demonstrated that CCR5 can mediate unique signaling events (14,15). In addition, we have shown that human Hsp70 from melanoma cells can chaperone tumor-associated peptides (tyrosinase) and deliver them to DCs allowing cross-presentation and T cell stimulation (16).…”
mentioning
confidence: 99%
“…6,7 CCR1 and CCR5 are expressed on various cell types implicated in atherosclerosis, eg, monocytes/macrophages, T lymphocytes, or Th1-type cells, and are special-ized in mediating RANTES-triggered arrest and transendothelial diapedesis of these cells. [7][8][9] Further to ligand binding and leukocyte attraction, these receptors can induce activation and detrimental effects of emigrated cells at the lesion sites. 10 RANTES is detectable in atherosclerotic plaques and deposited on early atherosclerotic endothelium by activated platelets, where it triggers arrest of circulating monocytes.…”
mentioning
confidence: 99%